(3aGFb GdCfXGQs ((3CMeO UdGM GdYjShi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi ehGgHg hfhGdg hGdgOGjI deYQaI MQGeg hMdGdg ebOeI Ci gPg SHYI aUhd ebOeI hgj HcSQ GdOGd HeYfi eJbOeg dCfgG JbOeJ Ydi Yde GdaQhY s
(3BNQgG (B:s
(3hbO GTGQ Edi gPG Hbhdg ajUjQ eNjQ hHJeGe gPg GdLedI JeJ GdebOeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdejcQhajde ZjQ ehLhO GfXQg eY GdhQbGJ ddLhjfi Qbe (B776 (3ai GdeQJH GdGHLOis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs